PENGARUH PROFITABILITY, KOMISARIS INDEPENDEN, KOMITE AUDIT, LEVERAGE, DAN CAPITAL INTENSITY RATIO TERHADAP TARIF PAJAK EFEKTIF (EFFECTIVE TAX RATE) (Studi Empiris pada Perusahaan Transportasi yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Delly Ria; M Rasuli; Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study to analize the effect of profitability, independent commissioner, audit committe, leverage, and capital intensity ratio to the Effective tax rate (Empiral Study on Transportation Companies listed in Indonesia Stock Exchange period 2012-2015).This study using purposive sampling technique in which this study took company data transportation listed on the Stock Exchange in the period 2012-2015. The population of this research were 33 companies with a selected sample of the sample is based on research criteria as many as 10 companies sampled. Multiple regresion is used to test the hypothesis. After it was tested by using SPSS version 23. The results of this study declare that the profitability, audit committe, and leverage has a significant impact on the effective tax rate. While independent commissioner and capital intensity ratio has no effect on the effective tax rate. Adjusted R Square shows the value of 0,241. It means that 24,1% change in the effective tax rate is affected by the determinant variables in the model. The small coefficient of determination in this study is caused by the independent variables tested that have a little relationship to the dependent variable.Keywords: Effective Tax Rate, Profitability, Independen Commissioner, Audit Committe, Leverage, and Capital Intensity Ratio